2007
DOI: 10.1111/j.1365-2818.2007.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging applications of synchrotron X‐ray phase‐contrast microtomography in biological morphology and biomaterials science. I. General aspects of the technique and its advantages in the analysis of millimetre‐sized arthropod structure

Abstract: SummarySynchrotron-generated X-rays provide scientists with a multitude of investigative techniques well suited for the analysis of the composition and structure of all types of materials and specimens. Here, we describe the properties of synchrotron-generated X-rays and the advantages that they provide for qualitative morphological research of millimetresized biological organisms and biomaterials. Case studies of the anatomy of insect heads, of whole microarthropods and of the three-dimensional reconstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(213 citation statements)
references
References 66 publications
1
209
1
1
Order By: Relevance
“…The morphology, functional role and phylogenetic relevance of the MET (also known as the metafemoral spring, metafemoral apodeme or Maulik's organ) have been extensively studied for flea beetles, tribe Alticini (Furth, 1980(Furth, , 1982(Furth, , 1988(Furth, , 1989Furth and Suzuki, 1990b, 1992, 1994, 1998Furth et al, 1983;Schmitt, 2004;Betz et al, 2007). It was proposed (see Introduction) that the MET is a spring-like specialized structure for the storage of elastic strain energy performed by its compression and dilation, resulting in a fast extension of the tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology, functional role and phylogenetic relevance of the MET (also known as the metafemoral spring, metafemoral apodeme or Maulik's organ) have been extensively studied for flea beetles, tribe Alticini (Furth, 1980(Furth, , 1982(Furth, , 1988(Furth, , 1989Furth and Suzuki, 1990b, 1992, 1994, 1998Furth et al, 1983;Schmitt, 2004;Betz et al, 2007). It was proposed (see Introduction) that the MET is a spring-like specialized structure for the storage of elastic strain energy performed by its compression and dilation, resulting in a fast extension of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…The model of the jumping mechanism in flea beetles proposed by Betz et al (2007) is the most detailed one and is based on modern micro-computed tomography (µCT) studies of the jumping apparatus as a whole. In brief, the flexor muscles adduct the tibia, then the flexor and the extensor muscles co-contract, the extensor muscles contract the MET and the energy of contraction is accumulated in the MET.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of other tomographic methods, particularly micro-MRI (Jacobs et al, 2003;Ruffins et al, 2007) and optical projection tomography (Kerwin et al, 2004;Sharpe, 2004), have been demonstrated convincingly, but the use of X-ray-based tomographic imaging has been constrained by the low intrinsic X-ray absorption of unmineralized tissue and the lack of established contrast agents. Phase contrast enhancement of X-ray images (Betz et al, 2007), while useable on unstained material, is much more useful for objects with distinct edges, rather than the softer gradients characteristic of embryos. Three-dimensional X-ray microscopy has been used to image subcellular structures (Larabell and Le Gros, 2004;Le Gros et al, 2005), but resolutions of tens of nanometers require a synchrotron source and a field of view too small to be of general utility to organismal developmental research.…”
Section: Introductionmentioning
confidence: 99%
“…This applies especially to sea urchins, where the strong X-rays have to penetrate the calcite endoskeleton twice, making the analysis of soft tissues in this taxon with conventional desktop µCT equipment practically impossible. However, more advanced CT methods such as synchrotron radiation tomography and very-high-resolution X-ray computed tomography have been shown to be capable of soft tissue imaging in specimens with strong endo-and exoskeletons (Tafforeau et al 2006, Betz et al 2007, Socha 2007. Unfortunately, the allocated scanning times at synchrotron facilites are extremely limited.…”
Section: Boesch 2001mentioning
confidence: 99%